1997
DOI: 10.1093/oxfordjournals.eurheartj.a015316
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology of venous thromboembolic disease: Results of a French Multicentre Registry

Abstract: Introduction-Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 19 publications
3
40
0
7
Order By: Relevance
“…The key acquired risk factors for VTE comprise trauma, surgery, prolonged immobilisation, advanced age, pregnancy and malignancy [1,2]. In the recently published French Multicenter Registry it was revealed that nearly 50% of PE and DVT cases occurred in the absence of a classical predisposing risk factor [3]. Within the last decade many investigators have focused on identifying congenital predisposition to thrombosis.…”
mentioning
confidence: 99%
“…The key acquired risk factors for VTE comprise trauma, surgery, prolonged immobilisation, advanced age, pregnancy and malignancy [1,2]. In the recently published French Multicenter Registry it was revealed that nearly 50% of PE and DVT cases occurred in the absence of a classical predisposing risk factor [3]. Within the last decade many investigators have focused on identifying congenital predisposition to thrombosis.…”
mentioning
confidence: 99%
“…Right heart thrombi are present in about 4% of patients with acute PE [1,3,4,6,11] but this rate increases to about 18% [2] to 22% [12] in patients hospitalized in intensive care units. In our centre, the rate of RiHT in patients with acute PE was about 2% (13 of 746 subsequent patients).…”
Section: Discussionmentioning
confidence: 99%
“…However, in almost one-half of cases, the underlying causal factor cannot be determined. In cases of DVT the most probable focus is the deep veins of lower extremities, but this cannot be proved in each case (8). The use of more sensitive diagnostic tools, such as magnetic resonance imaging, and performing ultrasonographic examinations as early as possible are very important (3).…”
Section: Discussionmentioning
confidence: 99%